Peran dan Tanggung Jawab Mediator dalam Penyelesaian Sengketa pada Era Modernisasi Hukum - Syaiful Khoiri Harahap (Jurnal Hukum Lex Generalis, 2025)
Mediation is an effort to accelerate dispute resolution with the assistance of a neutral third party who does not take sides with any of the disputing parties. In the era of legal modernization, dispute resolution is also carried out through the use of information technology, such as the possibility of conducting meetings online. The research method relies on normative legal research with a statutory approach and a conceptual approach. The findings show that mediation serves as an initial stage in dispute resolution. The Supreme Court has issued regulations governing mediation procedures to be conducted by mediators. As the key actors in the success of mediation, mediators are required to guide the parties more effectively in reaching a peaceful settlement, including through the use of information technology.